Scramble Learning Model Improves Pancasila Education Outcomes in Primary School : Model Pembelajaran Scramble Meningkatkan Hasil Pendidikan Pancasila di Sekolah Dasar - Zafirah; Abdulah; Hidayat, Puput Wahyu (Indonesian Journal of Innovation Studies, 2025)
General Background: Education serves as a foundation for developing human potential and character, with Pancasila Education being central to instilling national values in Indonesian schools. Specific Background: At SD Negeri 032/II Tanjung Gedang, traditional lecture-based methods resulted in low engagement and suboptimal outcomes in Pancasila Education. Knowledge Gap: Despite its success in other subjects, the Scramble learning model has rarely been applied in the context of Pancasila Education, leaving limited evidence of its effectiveness for civic and character education. Aim: This study aimed to evaluate the effectiveness of the Scramble learning model in improving fifth-grade students’ learning outcomes in Pancasila Education. Results: Using Classroom Action Research across two cycles with 20 students, results showed a marked increase in achievement: from 40% pre-research to 65% in Cycle I and 90% in Cycle II, demonstrating substantial learning gains and improved participation. Novelty: The study contributes by extending the application of the Scramble model beyond its common use in language learning, showcasing its value for civic education. Implications: These findings highlight Scramble as a promising instructional strategy for enhancing engagement, comprehension, and achievement in Pancasila Education, thereby supporting the broader goal of character formation in primary education.Highlight :  The Scramble model significantly improved student learning outcomes. Its application made learning more active and engaging. The study showed improvements in students’ character and understanding. Keywords : Scramble, Learning Outcomes, Pancasila Education, Primary School, Character Education